Intencionalidades, territorialidades e temporalidades da agroecologia e da agricultura orgânica em Itapejara d´Oeste, Salto do Lontra e Verê (SO PR) - Meira, Suzana Gotardo de (2013)
The environmental impacts caused by the industrialization of Agriculture is an argument to question the package, based on the domination of all life through economic and instrumental rationality. The Agroecology and organic agriculture, among other forms of alternatives to conventional agriculture, arises from the crisis of modernity. To carry out studies on these forms of production in some municipalities in the Southwest of Paraná, we realize discussions around this issue. The cities selected for this research were Itapejara d´Oeste, Salto do Lontra e Verê (PR), because they have some history with Agroecology and organic agriculture. So, we were able to make progress in discussions on the subject, proposing a typology to differentiate rural establishments who practice organic agriculture, those based on principles of Agroecology and apply this typology with farmers in the three municipalities. We also perform a geographical approach to the subject, seeking to seize rhythms, temporalities, territorialities and intentionality that characterize the Agroecology and organic agriculture developed in the cities surveyed. To achieve these objectives, the methodology consisted of bibliographic surveys of authors that discuss the concept of organic agriculture and Agroecology, and try to identificate internationalities and territorialities in a specific empirical reality. We conducted interviews starting from a pre-established screenplay, with farmers and representatives of partner institutions of the organic and agro-ecological production in Itapejara d´Oeste, Salto do Lontra and Verê (PR). Farmers who practice organic agriculture and Agroecology are entered into multiple territories, resulting from the coexistence of overlapping and their material and immaterial territorialities of different temporalities, which in turn are conditioned by the intentionality of these farmers and other social subjects. In this way, these farmers print their actions through time and territorialize the space where they live, creating and transforming their territorialities and temporalities.